2018
DOI: 10.1080/15548627.2017.1388476
|View full text |Cite
|
Sign up to set email alerts
|

MTA1 is a novel regulator of autophagy that induces tamoxifen resistance in breast cancer cells

Abstract: Tamoxifen is commonly used to treat patients with ESR/ER-positive breast cancer, but its therapeutic benefit is limited by the development of resistance. Recently, alterations in macroautophagy/autophagy function were demonstrated to be a potential mechanism for tamoxifen resistance. Although MTA1 (metastasis-associated 1) has been implicated in breast tumorigenesis and metastasis, its role in endocrine resistance has not been studied. Here, we report that the level of MTA1 expression was upregulated in the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 48 publications
1
64
0
1
Order By: Relevance
“…MiRs increasingly play a potential and core role in the regulation of the malignant development of cancer by acting as oncogenes or tumor suppressors [23]. Furthermore, Lee et al revealed that overexpression of MTA1 was linked to a higher tumor grade and resulted in poorer clinical outcomes in human breast cancer [24]. In this study, we investigated the effect of miR-183 on the invasion and metastasis of NSCLC by mediating MTA1 and found that the up-regulation of miR-183-induced MTA1 restrains the proliferation, EMT, migration and invasion of human NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiRs increasingly play a potential and core role in the regulation of the malignant development of cancer by acting as oncogenes or tumor suppressors [23]. Furthermore, Lee et al revealed that overexpression of MTA1 was linked to a higher tumor grade and resulted in poorer clinical outcomes in human breast cancer [24]. In this study, we investigated the effect of miR-183 on the invasion and metastasis of NSCLC by mediating MTA1 and found that the up-regulation of miR-183-induced MTA1 restrains the proliferation, EMT, migration and invasion of human NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, as a cellular process, is very important in cancer research. Recent studies have reported that many anticancer agents kill tumors by inducing autophagic cell death, such as tamoxifen, temozolomide and etoposide . In our previous study, we have found that magnolin suppresses human colorectal cancer cell growth via activating autophagy and cell cycle arrest.…”
Section: Discussionmentioning
confidence: 77%
“…Recent studies have reported that many anticancer agents kill tumors by inducing autophagic cell death, such as tamoxifen, temozolomide and etoposide. [41][42][43] In our previous study, we have found that magnolin suppresses human colorectal cancer cell growth via activating autophagy and cell cycle arrest. Inhibition of autophagy can markedly block magnolin-regulated cell cycle arrest and significantly abrogate magnolin-inhibited proliferation.…”
Section: Discussionmentioning
confidence: 95%
“…Through investigation in a 3D model, we found TAM at 10 Ī¼mol/L slightly increased cell death in nonā€invasion cells and had no effect in invasion cells, whereas it induced P62 degradation and mediated U87 cell spheroid autophagy, suggesting that this concentration can induce autophagy and low levels of apoptosis (Figure B). Papers reported that cells treated with TAM induced autophagy and then induced cell apoptosis or death . ERā€Ī±36 was highly expressed at the edge of the sphere, where there was more resistance for TAM than at the center of the sphere (Figures and ).…”
Section: Discussionmentioning
confidence: 99%